Neutron powder diffraction study of nuclear and magnetic structures of multiferroic (Bi 0.8Ba 0.2)(Fe 0.8Ti 0.2)O 3: Evidence for isostructural phase transition and magnetoelastic and magnetoelectric couplings - Singh A.; Senyshyn A.; Fuess H.; Chatterji T.; Pandey D. (My University, 2025)
We report here the results of a high-resolution neutron powder diffraction study on the multiferroic solid solution system (Bi 0.8Ba 0.2)(Fe 0.8Ti 0.2)O 3 in the temperature range 4 to 700 K. Using irreducible representation theory to analyze the magnetic structure by Rietveld refinement, we show that the magnetic structure is collinear G-type antiferromagnetic. Further, we confirm the occurrence of an isostructural phase transition (IPT) accompanying the magnetic ordering around ∼625 K in (Bi 0.8Ba 0.2)(Fe 0.8Ti 0.2)O 3. It is shown that as a result of the IPT, the positions of all the atoms change significantly in the magnetically ordered phase, leading to an excess polarization which scales linearly with the sublattice magnetization obtained by Rietveld refinement of the magnetic structure. Structural evidence for magnetoelastic coupling for the magnetic transitions below room temperature is also presented. © 2011 American Physical Society.